2014
DOI: 10.1037/a0037328
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child relationship quality moderates the link between marital conflict and adolescents’ physiological responses to social evaluative threat.

Abstract: This study examined how marital conflict and parent-child relationship quality moderate individual differences in adolescents' adrenocortical and autonomic nervous system (ANS) responses to social evaluative threat. Saliva samples (later assayed for cortisol and alpha-amylase, sAA) were collected from 153 youth (52% female; ages 10-17 years) before and after, and cardiovascular activity was assessed before and during, the Trier Social Stress Test (TSST). Marital conflict predicted higher levels of sAA reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 72 publications
(126 reference statements)
1
35
0
Order By: Relevance
“…Researchers studied salivary cortisol (11,28,3034,37 40 ,42 47,4954,5668,70,71) and/or salivary α-amylase response to stress (11,29,32,33,35,36,40–42 ,44 ,48,49,52,53,55,59 ,61,63,66,6972) for their association with CV/CM items. A substantial number of these studies showed significant correlations between salivary cortisol and/or salivary α-amylase and clinical/subclinical CV/CMR indicators (28,29,31,32,36,37,44,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers studied salivary cortisol (11,28,3034,37 40 ,42 47,4954,5668,70,71) and/or salivary α-amylase response to stress (11,29,32,33,35,36,40–42 ,44 ,48,49,52,53,55,59 ,61,63,66,6972) for their association with CV/CM items. A substantial number of these studies showed significant correlations between salivary cortisol and/or salivary α-amylase and clinical/subclinical CV/CMR indicators (28,29,31,32,36,37,44,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents from families with a history of interparental aggression showed a reactive response to the task, indicated by elevations in sAA, compared with adolescents from families with no family history of interparental aggression. In another study of responses to marital conflict, Lucas-Thompson and Granger (2014) also found that youth exposed to high levels of interparental conflict showed high levels of sAA reactivity to a stress task. Based on these data, it might be reasonable to hypothesize a positive association between youth’s victimization experiences and their sAA responses.…”
Section: Introductionmentioning
confidence: 90%
“…When activated, the HPA axis triggers the release of glucocorticoids, including cortisol, and the SNS releases catecholamines into circulation. Within the ANS, the SNS and parasympathetic nervous system (PNS) work in concert to regulate physiological arousal to stressors (Lucas-Thompson and Granger 2014). The ANS is responsible for “fight or flight” reactions and responds more quickly to acute stressors than the HPA axis.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, the results of this study are in line with theoretical perspectives that emphasize the importance of the family context for shaping individual differences in the set point of biobehavioral stress responses (Booth et al., ). Past research is mixed about whether marital conflict exposure is linked with dampened or heightened physiological reactivity (Ballard et al., ; Davies et al., ; El‐Sheikh, ; Lucas‐Thompson, ; Lucas‐Thompson & Granger, ). The results of the current study suggest that youth conflict appraisals play an important role in determining the nature of the association between conflict exposure and stress physiology.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that toddlers display heightened cortisol reactivity but older children display dampened cortisol reactivity (Davies, Sturge‐Apple, Cicchetti, & Cummings, ). In adolescents exposed to social–evaluative stress, marital conflict predicts dampened HPA and ANS functioning, in terms of cardiovascular and cortisol reactivity, respectively (Lucas‐Thompson, ) as well as heightened SNS (sAA) stress responses, particularly when conflict occurs in the context of poor‐quality relationships with parents (Lucas‐Thompson & Granger, ).…”
Section: Marital Conflict Exposure As a Stressormentioning
confidence: 99%